IL-4-Responsive B Cells Are Detrimental During Chronic Tuberculosis Infection in Mice - Parihar, Suraj P.; Ozturk, Mumin; Höft, Maxine A.; Chia, Julius E.; Guler, Reto; Keeton, Roanne; van Rensburg, Ilana C.; Loxton, Andre G.; Brombacher, Frank (Frontiers in Immunology, 2021)
In tuberculosis, T cell-mediated immunity is extensively studied whilst B cells received limited attention in humans and mice. Of interest, Mycobacterium tuberculosis (Mtb) does increase IL-4 Receptor-alpha (IL4Ra) expression in murine B cells. To better understand the role of IL4Ra expression in B cells, we compared wild type mice with B cell-specific IL4Ra-deficient mice (mb1creIL-4Rα-/lox mice) to understand the role of IL-4Rα signaling in B cells. Chronic Mtb aerosol infection in mb1creIL-4Rα-/lox mice reduced lung and spleen bacterial burdens, compared to littermate (IL-4Rα-/lox) control animals. Consequently, lung pathology, inflammation, and inducible nitric oxide synthase (iNOS) expression were reduced in the lungs of mb1creIL-4Rα-/lox mice, which was also accompanied by increased lung IgA and decreased IgG1 levels. Furthermore, intratracheal adoptive transfer of wild-type B cells into B cell-specific IL4Ra-deficient mice reversed the protective phenotype. Moreover, using constitutively mCherry expressing Mtb we showed decreased association with B cells from mb1creIL-4Rα-/lox mice ex vivo. In addition, supernatants from Mtb-exposed B cells of mb1creIL-4Rα-/lox mice also increased the ability of macrophages to produce nitric oxide, IL-1β, and IL-6. Together, this demonstrates that IL-4-responsive B cells are detrimental during the chronic phase of tuberculosis in mice with perturbed antibody profiles, inflammatory cytokines and stat1 levels in the lungs.